L'Archivio Edoardo Cavallini presso la Biblioteca del Conservatorio Luigi Cherubini di Firenze Inventario - Viapiana, Miriam (Saggi Cherubini, 2019)
Edoardo Cavallini (Florence, 1911-1968) was one of the most original and interesting personalities of the Italian music scene, but also one of the most overlooked. He was a prolific composer and a respected theorist, as well as a pioneer of modern microtonal (or, as he liked to call it, multicolour) music. The rich archive the Maestro left behind, which is currently kept at the Luigi Cherubini Conservatory of Florence, makes it possible to deepen the knowledge of his life and to restore his work, while at the same time granting him a posthumous, yet absolutely deserved recognition. This volume is intended as a navigation tool to be used among the documentary materials of his very rich archive, spacing from personal to official correspondence and passing through unpublished, handwritten notes.